KEABSAHAN WALI MUHAKKAM DALAM HUKUM ISLAMPERSPEKTIF IMAM SYAFI’I DAN SYAFI’YYAH (Tamaddun, 2021)
A happy marriage is everyone’s goal who are planning to married. To successfully achieve it, when husband and wife is married a legal marriage by a marriage guardian. The issue of guardianship of marriage has been conveyed by the Qur'an and al-Hadith, but related to the existence of muhakkam guardians it is not explicitly stated in the Qur'an or al-Hadith, so that there are different understandings among the scholars, especially between Imam Shafi'i, Abu Ishaq AshSyairozi and Imam Nawawi. The Syafi'i madhhab in determining the validity of a muhakkam guardian basically has the same essence, but in determining whether a muhakkam guardian is valid when marrying a prospective husband and wife, this is what inspires the author to conduct analysis and study in the concepts offered by Imam Shafi' i, Abu Ishaq Ash-Syairozi and Imam Nawawi. This research uses library research type with descriptive qualitative approach using primary and secondary data which is analyzed using content analysis method (content analysis). The results of the study say that: in looking at the guardian muhakkam between Imam Syafi'I and Syafi'iyah there are several kinds of formulations, including Wali Muhakkam in a review of Islamic law is allowed and legal to marry a woman with several conditions. In determining the guardian of Muhakkam, Imam Syafi'i and Imam Nawawi there is no difference. He both only requires that a Muhakkam guardian must be a just person. So this criterion is not different from the criteria for marriage guardians in general. But in the view of Abu Ishaq Asy Shirazi, the guardian of Muhakkam must be an expert in knowledge and Muhjtahid.